Prevalence and associated factors of malnutrition among adult hospitalized patients at Amhara National Regional State Referral Hospitals, Ethiopia. Issue 3 (2015) - Haile, Alemtsehay; Hailu, Mignote; Tesfaye, Eleni
No abstract available